Kelan järjestämän kuntoutuksen kohdentuminen ja vaikutukset työkykyyn kunnallisilla työpaikoilla - Suoyrjö, Heikki, 1952- (Helsinki : Kelan tutkimusosasto, 2010)
Inriktningen hos rehabiliteringstjänster ordnade av Folkpensionsanstalten i Finland och deras inverkan på arbetsförmågan på kommunala arbetsplatser.
Allocation of rehabilitation measures provided by the Social Insurance Institution of Finland and its efects on work disability among local government employees.
Sammandrag: Inriktningen hos rehabiliteringstjänster ordnade av Folkpensionsanstalten i Finland och deras inverkan på arbetsförmågan på kommunala arbetsplatser.
Abstract: Allocation of rehabilitation measures provided by the Social Insurance Institution of Finland and its effects on work disability among local government employees.
Tiivistelmä.
Abstract: Allocation of rehabilitation measures provided by the Social Insurance Institution of Finland and its efects on work disability among local government employees.
Artikkeliväitöskirjan yhteenveto-osa ja 4 eripainosta.
Väitöskirja
Keywords: Suomi. -- Kansaneläkelaitos; Occupational Health; Rehabilitation; Fibromyalgia; Occupational Diseases; Chronic Disease; Back Pain; Neck Pain; Disabled Persons; Insurance, Disability -- economics; Insurance, Disability -- statistics & numerical data; Sick Leave -- economics; Sick Leave -- statistics & numerical data; Insurance, Health -- economics; Rehabilitation, Vocational -- economics; Analgesics; Drug Utilization; Treatment Outcome; kuntoutus; vaikutukset; työkyky; kohdentaminen; tuki- ja liikuntaelinten taudit; fibromyalgia; sairauspoissaolot; työkyvyttömyyseläkkeet; työkyvyttömyys; vaikuttavuus; tuki- ja liikuntaelimet; Aslak-toiminta.; kunnan työntekijät; arbetsförmåga; sjukfrånvaro; invalidpensioner; rörelseorganens sjukdomar; fibromyalgi; rehabilitering (vård); Aslak-verksamhet.; Academic Dissertation